PENGARUH FRAMING, URUTAN BUKTI AUDIT DAN SKEPTISME AUDITOR TERHADAP AUDIT JUDGMENT DENGAN KOMPLEKSITAS TUGAS SEBAGAI VARIABEL MODERASI - Sri Ayem; Sya'iv Putri (JURNAL ILMIAH EDUNOMIKA, 2021)
This study aims to examine the effect of framing, sequence of audit evidence and auditor skepticism on audit judgment with task complexity as a moderating variable. The theory used to test this research is prospect theory and adjustment model theory. The data used are primary data with the research method used, namely a questionnaire. The nature of this research is a quantitative study because the research conducted to test the proposed hypothesis is to test the effect of the independent variable on the dependent variable. The results of this study indicate all variables have a positive effect on Audit Judgment. Keywords: Framing; Audit Evidence Sequence; Auditor Skepticism; Audit Judgment and Task Complexity